Konseptualisasi Adventure-Based Counseling untuk Meningkatkan EcoWellness: Mengintegrasikan Alam dan Petualangan untuk Kesejahteraan Klien yang Holistik - Lakadjo, Mohamad Awal (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
The aim of this research describes a conceptual effort to improve clients' holistic EcoWellness through adventure-based counseling that is integrated with nature and adventure. Integrating Adventure-based Counseling activities with the concept of EcoWellness, namely appreciation, respect, admiration, and connectedness to nature, has been proposed as an effective framework for enriching the concept of counseling theory. The research method uses a literature review to review logically based on a comprehensive understanding of the conceptual framework of Adventure-based Counseling to improve EcoWellness. Research goes through six stages, namely (1) selecting and determining the topic; (2) developing tools for argumentation and conclusions from various concepts; (3) literature search to find sources relevant to the specified topic with the help of Mendeley Reference Manager to catalog and document information; (4) a literature survey was conducted to collect, organize, and analyze data that had been collected and documented in Mendeley Reference Manager; (5) criticizing the literature, producing responses to the research topic, a conceptual framework as a conclusion to form research objectives; and (6) writing a review, the review produces a document. To explore this concept, this research investigates the role of nature in strengthening humans' connection to the environment, as well as the positive impact of adventure in enhancing EcoWellness. The findings of this literature review highlight the importance of integrating nature and adventure in counseling to achieve clients' holistic balance. The theoretical implications of this conceptualization are discussed in the context of improving the quality of counseling services and a deeper understanding of humans' relationship with nature